PERANCANGAN SISTEM INFORMASI PENGOLAHAN IURAN SPP SISWA PADA SD IT AL- KHAIRAAT MENGGUNAKAN PHP DAN MySQL - Devi Iryanti; Erfanti Fatkhiyah (Jurusan Informatika INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA, 2015)
Monthly spp payments have significant roles in supporting an operational educational institutions.Primary integrated islamic al-khairaat still apply the payment system manually, so it needs of the system is. Computerized Problems in payment spp are arrears and payments spp not timely.bBased on it, writers will develop an information systems spp payments and using php mysql from the primary schools integrated islamic chamberlain al-khairaat that spp easily and quickly in making information in computerized. Features available in this system could be handle payment so it is more help officers a payment handle processes and data processing payment so will not happen double working, data relating to spp payments in computerized stored on database can do storage, conversion, the removal and search data and, reports and can produce proof of payment for students, in the form of kwitansi that can be taken when their spp payments as the report to students.